Breaking internalized teacher scripts: From traditional habits of mind to a creative mindset. Issue 3 (1st September 2014) - Rufo, David
This article tells the story of an elementary school math teacher faced with the challenge of preserving a classroom devoted to innovative and creative learning, as his independent day school moved towards standardization and traditional educational approaches. After being informed that his instruction needed to come into closer alignment with the rest of the school he invited his students to brainstorm ways in which they could inconspicuously remain empowered agents of their own learning. The class decided to set aside one hour each week as a time for self-directed learning. During this time they produced math-based carnival games culminating in an event they called 'Math Palooza'. Reflecting on this experience, the author realized the importance of using critical self-reflection to interrogate the status quo and as a safeguard from falling into habitualized methods of instruction and obsolete forms of curricular design.